Relation of neutrophil/lymphocyte ratio to resistant hypertension - Dağlı, Necati; Doğdu, Orhan; Şenarslan, Ömer; Yücel, Hasan; Kaya, Hakki; Akpek, Mahmut; Eriten, Semih (My University, 2016)
Objectives. Resistant hypertension has unfavourable effects on cardiovascular and other systems. The aim of this study was to investigate the association of neutrophil/lymphocyte (N/L) ratio and resistant hypertension. Methods. A total of 140 patients were included in the study. Ambulatory 24-hour blood pressure monitoring, transthoracic echocardiography and blood sample analyzing were performed in all patients. There were 60 patients with resistant hypertension group (mean age=55.1±9.7 years) and 80 patients with non-resistant hypertension group (mean age=56.8±14.1 years). Results. Mean neutrophil levels were significantly higher in resistant hypertension group (71.7±6.1% vs. 65.9±5.4%, p<0.001), while lymphocyte levels were significantly higher in non-resistant hypertension group (22±4.7% vs. 17.5±4.1%, p<0.001). N/L ratio was significantly higher in resistant hypertension group (4.3±1.2 vs. 3.1±0.9, p<0.001). In multivariate analysis, diabetes mellitus (odds ratio [OR]=2.857; 95% confidence interval [CI], 1.349-6.053; p=0.006), N/L ratio (OR=2.699; 95% CI, 1.821-4.002; p<0.001) and obesity (OR=3.429; 95% CI, 1.675-7.019; p=0.001) were independent predictors of resistant hypertension. Conclusion. The N/L ratio, which is cheaply and easily measurable laboratory data, is independently associated with resistant hypertension.
Keywords: Neutrophil/lymphocyte ratio; ambulatory blood pressure monitoring; Resistant hypertension